Development of leak-before-break filament wound composite structures. - Loukodimou, Vasiliki (Cranfield University, 2019)
A leak-before-break (LBB) concept was developed for composite pressure vessels (CPVs) to achieve a safe, predictable and controllable way of failure preventing the consequences of a catastrophic rupture. Artificial defects were introduced in the structure in prearranged patterns, acting as weak areas and enforcing failure initiation and propagation from these locations. A continuum damage constitutive model was developed through testing and simulation of tensile and compression specimens at [0°]8, specimens under cyclic in-plane shear at [±45°]2s, [+45°]₈ and [±67.5°]₂s as well as out-of-plane specimens at [0°]₁₀ and [0°]₁₂. A methodology was established for the introduction of artificial defects in the composite material for its failure control considering fibre cuts and interfacial defects. The LBB concept was investigated through the simulation of the behaviour of CPVs including defects under internal pressurisation. The assessment of the LBB behaviour was based on the ability to discern between the occurrence of two leakages; the first associated to the leakage phenomenon for pressure relief in the case of over-pressurisation and the second corresponding to ultimate failure. The influence of size and degree of damage induced through the defects was investigated, as well as the use of local reinforcing patches to enhance the LBB behaviour. The most suitable design for the optimal function of the LBB behaviour involves a circular fibre cut defective area of 87.5% fibre cut damage which results in a clear separation between leak and damage by a pressure difference of about 280 bar. The selected case was used for the manufacturing of a closed-end loaded composite pipe to validate the concept. The results of the testing showed that leakage did not occur from the introduced weak points due to manufacturing defects; however, the prediction of the damage initiation from the introduced defects was accurately identified with a difference of 2% compared to the simulation results.
Keywords: Composite pressure vessels; internal pressurisation; artificial defects; leak-before-break; damage model; continuum damage constitutive model